Bulfinch's Mythology - Bulfinch, Thomas ([Place of publication not identifed] : Canterbury Classics, 2014)
Summary: Can't keep all your gods and goddesses straight? Wondering about mythological references in classic literature? Bulfinch's Mythology offers approachable accounts of ancient legends in a compilation of the works of Thomas Bulfinch, banker and Latinist. This volume includes all three of Bulfinch's original titles: The Age of Fable, The Age of Chivalry, and The Legends of Charlemagne. Bulfinch states his purpose for the book clearly:?Our work is not for the learned, nor for the theologian, nor for the philosopher, but for the reader of English literature?w
Keywords: MYTHOLOGY